Teamwork in the Perspective of Islamic Education Management - Hadini, Hadini; Masbur, Masbur; Hayati, Hayati; Nurbayani, Nurbayani (Al-kayyis: Journal of Islamic Education, 2024)
Teamwork in Islamic education management is so urgent. This is because it is one of the things that determines whether or not the process of implementing Islamic education runs, which in turn will determine whether or not the goals that have been designed are achieved. In this study, researchers conducted a library research method. Here the researcher searches for literature in the form of books, research results, and journals, both national and international, related to the topic being studied. From the results of the study conducted, several important findings were found, including: First: the benefits of teamwork include the emergence of responsibility for quality management, time utilization, overseeing management, channeling information, in education management. Teamwork is beneficial for service users, students will be able to access information more easily, increase members' understanding, and can foster trust for its members. Second, optimizing the role of teamwork, providing opportunities to solve problems, involving all staff, training in problem-solving methods, supervision and providing rewards. Third, the Quran hints at the importance of teamwork, such as the example of the bee organization, so that the Quran enshrines the name An-Nahl in the letter, while the apostle in his history has translated teamwork when carrying out the migration strategy.